Assessing China's agricultural water use efficiency in a green-blue water perspective: A study based on data envelopment analysis. (January 2019) - Geng, Qingling; Ren, Qingfu; Nolan, Rachael H.; Wu, Pute; Yu, Qiang
Graphical abstract: Highlights: Provincial agricultural WUE was assessed based on data envelopment analysis in China. We compared the results between the blue-only and the green-blue scenarios. The lower potential can be improved under the green-blue scenario while higher potential for blue-only scenario. The pure technical efficiency was higher under the green-blue scenario in Northern provinces. Improving blue water use in NC and green water use in SC is a priority to enhance national WUE. Abstract: Uneven water resources and growing food demand due to an increasing population bring challenges to China. One important mechanism to address these challenges is to enhance water use efficiency (WUE). This requires information on current efficiencies in water use for agricultural production. In this study, we provide a benchmarking tool to assess relative agricultural WUE in 31 provinces in China during 2003-2013. Data Envelopment Analysis (DEA) was used with both green-blue water and blue-only scenarios. Results show that China's agricultural WUE has improved evidently after 2008. Overall technical efficiency (TE) and the pure technical efficiency (PTE) in China based on the green-blue scenario are relatively high, with the average potential increase less than 10% (8% and 4%, respectively). However, there is a larger potential for blue water use efficiency (14% and 7% respectively). The PTE in Northern China (NC) is higher than that in Southern China (SC) while the TE in NC is lower under green-blue scenario. Moreover, the TE and PTE in NC are lower than that in SC under blue-only scenario. These results indicate that green water management techniques in NC are superior to SC but the scale efficiency (SE) in NC is lower. There are four provinces where the efficiency values are on the frontier in four cases, i.e. two scenarios (green-blue and blue-only) and two assumptions in DEA, but fourteen provinces where the efficiency values are not on the frontier in any case and most of them were located in SC. Our results also suggest that improving SE can substantially contribute to national WUE, but exploring the solutions to enhance blue water use efficiency in China is also a key task in the future works. The research results have important implications for China and different provinces to improve agricultural WUE by water policies and management.